Usability Evaluation of English Learning Application Base on Augmented Reality Using ISO 9241 - Imam Fahrur Rozi; Eka Larasati; Vivin Ayu Lestari; Nurizal Dwi Priandani (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
Augmented Reality (AR) technology is one of the educational applications that may be created. AR is a learning tool that may be used to integrate virtual things or objects into a natural environment to engage in real-time. English is a foreign language that must be learnt. For language assistance, pupils must acquire a sufficient command of vocabulary via reading and listening exercises. Two factors contribute to the ineffectiveness of oral communication: pupils who do not have enough vocabulary knowledge and students who do not know how to employ vocabulary non their spoken language. One of the learning media that has been developed is the AR-based English vocabulary learning application which was developed in early April 2020 to September 2020. This application aims to help elementary school students (6-12 years) in learning English vocabulary. Where in the current learning which is due to the pandemic thus making distance learning. The purpose of this study is to measure the usability of the application whose vocabulary has been developed from three aspects, namely effectiveness, efficiency and user satisfaction (ISO 9241). The results of the research conducted show that the usability level of this application is 89% effectiveness, 94% efficiency and 91% user satisfaction. So that this learning application can be said to have good usability and can be used as a supporting medium for learning English vocabulary for children aged 6-12 years independently.